Planar array antenna for WPT system at 2.4 GHz - Pookkapund, Khanet; Boonying, Komkris; Dentri, Sitthichai; Phongcharoenpanich, Chuwong (My University, 2015)
This paper presents a rectifying antenna (rectenna) which can harvest the wireless power at 2.45 GHz band. The proposed antenna is designed to convert the wireless RF signal into DC power. The antenna structure consists of four printed dipoles located perpendicularly to one another to combine the pattern and increase the gain. The compact antenna radiates unidirectional pattern with the high gain. The rectifying circuit part is designed based on voltage diode with stub matching circuit.
Keywords: Planar Antenna; Rectenna; Rectifying circuit; Wireless power transmission